2022
DOI: 10.3991/ijep.v12i1.24571
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Engineering Technology Students’ Digital Footprints in Synchronous and Asynchronous Blended Courses

Abstract: The advent of Covid-19 provided an enormous academic and logistical challenge to almost all academic institutions in the United States and around the world. As a precautionary measure surrounding the novel coronavirus and in line with recommendations from the Center for Disease Control and Prevention (CDC) at that time (spring 2020), most higher education institutions in the United States shut down campuses and completed the second half of the spring 2020 semester virtually. During the fall 2020 semester, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In this sample, the papers [6, 24, 66] deal with the online setting, covering the Remember, Understand, Apply and Analyze levels of the Bloom's taxonomy for remote activities, in accordance with the Figure 10. Instead, [58] and [62] focus on the Rotation learning approach, while [70] and [62] focus on the Labs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sample, the papers [6, 24, 66] deal with the online setting, covering the Remember, Understand, Apply and Analyze levels of the Bloom's taxonomy for remote activities, in accordance with the Figure 10. Instead, [58] and [62] focus on the Rotation learning approach, while [70] and [62] focus on the Labs.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 summarizes the distribution of the papers according to the country of application reported in the papers. What emerges, from the chart is that the country with the highest number of studies is Spain ( 14), followed by Australia (9), the United States (8), India (6) and others. If we consider a continental perspective, Europe is the one with the highest number of studies on the topic.…”
Section: Country Distributionmentioning
confidence: 98%
“…Thus, according to a study of the G2R group, led by Imed Bouchrika, PhD, online learning emerged as a safe and viable option for education continuity as the COVID-19 pandemic turned personal and professional worlds upside down [3]. The development of distance learning technologies contributes to the diversification and spread of blended learning, which is considered to be the best for teaching and learning in secondary schools [4] and higher educational institutions [5], [6]. However, the issue of selecting a model of blended learning in higher educational institution requires a separate study.…”
Section: Introductionmentioning
confidence: 99%
“…The researcher found that the blended learning experiences had a high level of impact on students' long-term learning and their twenty-first century skills. P. Appiah-Kubi et al [6] describe the study which was initiated to learn about the level that Engineering Technology students engaged with online course materials using Zoom and Learning Management System. Researchers point out that Engineering Technology programs incorporate a lot of laboratory and hands on modules.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that online learning provides new effective tools for higher education and presents the potential for improving the knowledge, skills and learning effectiveness of future engineers. Establishing a balance between synchronous and asynchronous teaching units can mediate the necessary interaction among students while taking advantage of all the potential benefits of blended learning [2]. Research by these authors has clearly established that those students who performed well demonstrated a minimum 44% engagement rate with the course content.…”
Section: Introductionmentioning
confidence: 99%